Complete esophageal obstruction following endoscopic variceal band ligation - Abhijit Bhatia; Carlton Sexton; Anita Ahmed; Harjit Chahal (Greater Baltimore Medical Center, 2013)
Variceal hemorrhage is a potential complication of portal hypertension. Besides medical management, endoscopic variceal band ligation (EVBL) has emerged as a promising prophylactic tool proving to be superior to sclerotherapy. EBVL is a simple procedure associated with minor complications and short recovery time. In this report, we present a case of a rare complication of complete esophageal obstruction following an EVBL procedure. Given the high numbers of such procedures performed, it is imperative that internists and specialists be aware of this unusual complication.